Dendrite‐Free and Long‐Cycling Lithium Metal Battery Enabled by Ultrathin, 2D Shield‐Defensive, and Single Lithium‐Ion Conducting Polymeric Membrane. Issue 33 (13th July 2022) - Liu, Qiantong; Liu, Ruliang; Cui, Yin; Zhou, Minghong; Zeng, Junkui; Zheng, Bingna; Liu, Shaohong; Zhu, Youlong; Wu, Dingcai
Abstract: Polymeric membranes are considered as promising materials to realize safe and long‐life lithium metal batteries (LMBs). However, they are usually based on soft 1D linear polymers and thus cannot effectively inhibit piercing of lithium dendrites at high current density. Herein, single lithium‐ion conducting molecular brushes (GO‐ g ‐PSSLi) are successfully designed and fabricated with a new 2D "soft–hard–soft" hierarchical structure by grafting hairy lithium polystyrenesulfonate (PSSLi) chains on both sides of graphene oxide (GO) sheets. The ultrathin GO‐ g ‐PSSLi membrane is further constructed by evaporation‐induced layer‐by‐layer self‐assembly of GO‐ g ‐PSSLi molecular brushes. Unlike conventional soft 1D linear polymeric structure, the rigid 2D extended aromatic structure of intralayer GO backbones can bear the shield effect of preventing the dendrites possibly generated at high current density from piercing. More importantly, such a shield effect can be significantly strengthened by layer‐by‐layer stacking of 2D molecular brushes. On the other hand, the 3D interconnected interlayer channels and the soft single lithium‐ion conducting PSSLi side‐chains on the surface of channels provide rapid lithium‐ion transportation pathways and homogenize lithium‐ion flux. As a result, LMBs with GO‐ g ‐PSSLi membrane possess long‐term reversible lithium plating/striping (6 months) at high current density. Abstract : Novel ultrathin shield‐defensive polymeric membrane obtained by layer‐by‐layer stacking of 2D molecular brushes is successfully utilized to achieve long‐cycling lithium metal batteries. For the molecular brushes, single lithium‐ion conducting side‐chains facilitate uniform lithium deposition, and rigid 2D extended aromatic backbones provide a superb layer upon layer protection function to prevent the dendrite growth at high current densities.